2020
DOI: 10.1177/1073858420916452
|View full text |Cite
|
Sign up to set email alerts
|

Integrating TMS, EEG, and MRI as an Approach for Studying Brain Connectivity

Abstract: The human brain is a complex network in which hundreds of brain regions are interconnected via thousands of axonal pathways. The capability of such a complex system emerges from specific interactions among smaller entities, a set of events that can be described by the activation of interconnections between brain areas. Studies that focus on brain connectivity have the aim of understanding and modeling brain function, taking into account the spatiotemporal dynamics of neural communication between brain regions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 108 publications
1
23
0
Order By: Relevance
“…Data evaluating EEG sources with low-resolution electromagnetic tomography (LORETA) are scarce. Thus, the current study aims to evaluate changes in functional connectivity of EEG frequency bands, with special emphasis on theta power in the prefrontal cortices as a result of rTMS (Esposito et al, 2020). This explorative study consists of four males between the age of 21 and 76, mean 52, SD = 23.84.…”
Section: Jeff Tarrantmentioning
confidence: 99%
“…Data evaluating EEG sources with low-resolution electromagnetic tomography (LORETA) are scarce. Thus, the current study aims to evaluate changes in functional connectivity of EEG frequency bands, with special emphasis on theta power in the prefrontal cortices as a result of rTMS (Esposito et al, 2020). This explorative study consists of four males between the age of 21 and 76, mean 52, SD = 23.84.…”
Section: Jeff Tarrantmentioning
confidence: 99%
“…The majority of studies on brain connectivity have been obtained from stand-alone unimodal neuroimaging methods (Plis et al 2011). We proposed the use of an integrative approach with a combination of different methods (Bergmann et al 2016) composed of structural and functional magnetic resonance imaging (MRI and fMRI, respectively), diffusion-weighted imaging (DWI), and transcranial magnetic stimulation and electroencephalography (TMS-EEG) coregistration (Bortoletto et al 2021;Esposito et al 2020;Levy-Lamdan et al 2020;Momi et al 2021;Voineskos et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Speci cally, accumulated studies found that the entire brain was affected through the thalamocortical and corticocortical connectivity (Aghakhani et al, 2004;Blumenfeld et al, 2003;Gotman et al, 2005). Functional connectivity (FC) is the statistical correlation between different brain regions in terms of information processing and structural connectivity (SC) (Esposito, Bortoletto, & Miniussi, 2020). Diffusion tensor image (DTI) is often used to construct the SC based on the white matter traction, and to investigate the mechanism in healthy brain and/or disorders (Gong et al, 2019;Jiang et al, 2020;Xue et al, 2014).…”
Section: Introductionmentioning
confidence: 99%